Biocorrosion and biomechanical analysis of vascular stents - Halwani, Dina O.; Brott, Brigitta C.; Lemons, Jack E.; Anderson, Peter G.; Anayiotos, Andreas; Kapnisis, Konstantinos (My University, 2011)
Despite advances in endovascular stent design, stent structural integrity and in-stent restenosis remains a significant clinical problem worldwide. The role of stent corrosion and metallic ion release has not been thoroughly studied and little attention has been given to the interaction of stent materials with the surrounding vessel wall and the mechanical forces involved after implantation. Our recent studies on Stainless Steel (SS), Cobalt-Chromium (CoCr) and Nickel-Titanium (NiTi) stents obtained from a tissue retrieval resource from cadavers with accompanying clinical histories, have revealed that these stents undergo corrosion in vivo, with significant release of metallic ions into surrounding tissues [1]. It is believed that high concentrations of metal ions from stents are toxic to vascular smooth muscle cells [2] and stimulate both inflammatory and fibrotic reactions leading to neointimal formation and a predisposition to device failure [3]. When this is combined with altered biomechanics of flow and motion, it creates a favourable environment for the development of restenosis. To separate the mechanical effects from the local environmental effects on the stent surface, we performed in-vitro mechanical studies on various combinations of stents under low and high curvature and in overlapping positions to compare the results of fretting, pitting and gouging with the explanted stents.
Keywords: Stent corrosion; Metallic ion; Stainless steel; Cobalt-chromium; Nickel-titanium